Commoning mobility in the age of COVID-19: a dialogue between Anna Nikolaeva and Jan Duffhues. Issue 3 (3rd July 2022) - Nikolaeva, Anna; Duffhues, Jan
ABSTRACT: In this dialogue the notion of "commoning mobility" is central. Anna Nikolaeva and Jan Duffhues both work on mobility issues in the city of Amsterdam – Anna as a mobility scholar at the University of Amsterdam and Jan as an innovation strategist at the municipality of Amsterdam. Each from their own professional perspective, they see the possibility of a new way of thinking about transitioning to more sustainable and inclusive mobilities. The notion of "commoning mobility" appears to capture that new way of thinking, yet many questions are open regarding its practical application. In this dialogue they together reflect on what "commoning mobility" might mean in practice, the role of different societal actors in it, the potential pitfalls of "commoning", and the impact of the global pandemic on our relationship with mobility.